2005
DOI: 10.1016/j.progsurf.2005.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of surface segregation in bimetallic Pt–M alloy nanoparticles (M=Ni,Re,Mo)

Abstract: -This review addresses the issue of surface segregation in bimetallic alloy nanoparticles, which are relevant to heterogeneous catalysis, in particular for electrocatalysts of fuel cells. We describe and discuss a theoretical approach to predicting surface segregation in such nanoparticles by using the Modified Embedded Atom Method and Monte Carlo simulations. In this manner it is possible to systematically explore the behavior of such nanoparticles as a function of component metals, composition, and particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 55 publications
4
56
0
Order By: Relevance
“…It is very important to analyze in this figure that the Pt and Pd atoms are distributed randomly; it is also possible to observe some surface segregation of the Pt atoms in the bimetallic nanoparticle. The main factors influencing the surface segregation process are determined by atomic size, heat of solution of the alloy and the difference in the surface energies of the pure metal 42 . However, in the case of Pt-Pd alloys, atomic size and heat of solution effects for surface segregation can be neglected because the heat of solution of the alloy is very small; besides the Pt and Pd atoms have similar sizes.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
“…It is very important to analyze in this figure that the Pt and Pd atoms are distributed randomly; it is also possible to observe some surface segregation of the Pt atoms in the bimetallic nanoparticle. The main factors influencing the surface segregation process are determined by atomic size, heat of solution of the alloy and the difference in the surface energies of the pure metal 42 . However, in the case of Pt-Pd alloys, atomic size and heat of solution effects for surface segregation can be neglected because the heat of solution of the alloy is very small; besides the Pt and Pd atoms have similar sizes.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
“…While a large number of elemental atom types can nowadays indeed be modeled using these potentials, constructing parametrizations for combinations of elements turns out to be more complex. In the context of combined catalyst/support systems, examples of available parametrizations include the COMB parametrization for {Si, Cu, Hf, Ti, O, their oxides and Zn, Zr and U} [51], and for {H, C, N, O, Cu, Ti, Zn, Zr} [58], MEAM parametrizations for {Al, Si, Mg, Cu and Fe alloys} [53,54], and a variety of binary and ternary Pt-alloys [53,54,92], and ReaxFF parametrizations for {Bi/Mo/O} [93] and {Mo, V, O} [94].…”
Section: Development Of Reactive Potentials For Catalysts and Catalysmentioning
confidence: 99%
“…Chepulskii et al [171] within Monte Carlo simulations reveal that in PtFe alloy first surface layer Pt segregation is compensated by Pt depletion in the second subsurface layer. Within Modified embedded atom method and montecarlo method Wang et al [172] reported three trends in Pt-Re, Pt-Ni and Pt-Mo systems (see figure 19). Starting with the Wullf's form (truncated polyhedron with a magic number of 586 atoms), the authors found a simple core/shell structure in P t 75 Re 25 with the outermost layer platinum rich while, the strong ordering tendency of Pt and Ni leads to P t 75 N i 25 NPs forming a surface-sandwich structure in which the Pt atoms are strongly enriched in the outermost and third layers while the Ni atoms are enriched in the second layer.…”
mentioning
confidence: 99%